PERANCANGAN SISTEM INFORMASI PENGGAJIAN BERBASIS WEB PADA PT. WIBEE INDOEDU NUSANTARA - Iedam Fardian Anshori; Ali Mulyawan (STMIK Mardira Indonesia, Bandung, 2021)
Payroll or salary management is a process of remuneration by an organization to employees as someone who contributes to the achievement of organizational goals. Employee payroll data processing system at Pt. Wieebu Indoedu is still simple. Each month's employee data is still recorded in a special book, and to submit proof of salary reports is still conventional. The problem that arises is the inconsistency of data that can cause data duplication, if the search for data takes a very long time because it still uses conventional systems, and data security is still not guaranteed. Therefore, the authors make a web-based payroll information system design. The method used is the waterfall method using system developer tools in the form of ERD and LRS. The design of this system is a solution to solving problems that occur in the payroll process at Pt.Wieebu Indeedu, with this system making activities more effective and efficient in work. Keywords: Payroll, data processing, Information system, waterfall.DOI : http://doi.org/10.5281/zenodo.4958277